Pengaruh Kualitas Produk dan Citra Merek Terhadap Loyalitas Konsumen (Studi Kasus Mahasiswa Pengguna Eiger Universitas Hasyim Asy’ari) - Alfin Dana Perkasa (BIMA : Journal of Business and Innovation Management, 2019)
This research is a quantitative research with survey method. The population in this study were students of Eiger University of Hasyim Asyari. The sampling technique uses saturated sampling with a total sample of 74 students. Data collection techniques using a questionnaire that has been tested for validity and reliability. The classic assumption test includes the normality test, the heteroscedasticity test, and the multicollinearity test and multiple linear regression analysis to test and prove the research hypothesis. The results of the t-test (partial) showed that the product quality variable (X1) had a positive and significant effect on consumer loyalty (Y) and the brand image variable (X2) had a positive and significant effect on consumer loyalty (Y). The results of the F test (simultaneous) showed that the product quality (X1) and brand image (X2) as a whole had a simultaneous and significant effect on consumer loyalty. (Y).